Association of the planetary health diet score with obesity, high blood pressure, dyslipidemia, and cardiometabolic risk markers: Using data from the 2016–2020 Korea National Health and Nutrition Examination Survey - Ujin Lee; Eugene Kang; Bomi Kim; Diana Shubekova; Adiyasuren Dookhuu; Heejin Lee; Jung Eun Lee; Minji Kang (PLoS ONE, 2026)
Noncommunicable diseases (NCDs) remain the leading cause of death worldwide, with unhealthy diets and insufficient physical activity as major contributing factors. The Planetary Health Diet is a sustainable dietary pattern linked to chronic diseases, but studies in Asian populations remain limited. Therefore, the aim of this study was to investigate the associations between the Planetary Health Diet score and cardiometabolic risk factors among Korean adults. We used KNHANES 2016–2020 data (n = 25,336), and the Planetary Health Diet score was calculated in accordance with the Lancet Commission guidelines. Participants were categorized into quartiles according to the Planetary Health Diet score, and multivariable logistic regression models were used to examine associations with obesity, hypertension, dyslipidemia, an elevated triglyceride-to-HDL cholesterol ratio, impaired fasting glucose, and an elevated HbA1c level. A higher Planetary Health Diet score was significantly associated with lower odds of hypercholesterolemia in women and was related to reduced prevalence of abdominal obesity, hypertension, low HDL-cholesterolemia, and elevated glycated hemoglobin (HbA1c) depending on age group. No significant associations were observed in men. These findings suggest that higher Planetary Health Diet scores may be associated with selected cardiometabolic markers among Korean women. Further research is warranted to confirm the applicability of the Planetary Health Diet score in Korean dietary contexts.